PENGARUH HUMAN, ORGANIZATION DAN TECHNOLOGY TERHADAP NETBENEFIT SISTEM INFORMASI MANAJEMEN LOGISTIK VAKSIN SIMDIO DAN SMILE DI KABUPATEN DEMAK - Siti Chanifah; Nining Handayani; Achmad Dheni Suwardhani (Journal of Innovation Research and Knowledge, 2026)
The digital transformation of the vaccine logistics management information system is expected to improve the effectiveness and efficiency of immunization services. The Demak District Health Office uses two systems, SIMDIO and SMILE, which still face obstacles in their implementation. This study aims to analyze the influence of human, organization, and technology on the net benefit of both systems using the HOT-Fit approach. A quantitative study with an analytical survey design and cross-sectional approach was conducted in October–November 2025. There were 32 respondents from 26 community health centers and the Health Office, for a total sample of 27 units. Data analysis used descriptive statistics and multiple linear regression with SPSS. Partial tests showed that in SIMDIO, the human variable (sig. 0.938) and organization variable (sig. 0.964) and technology variable (sig. 0.002). In SMILE, the human variable (sig. 0.132) and organization variable (0.964) and technology variable (sig. <0.001). Simultaneous tests (F-tests) showed that the three independent variables simultaneously had a significant effect on the benefits of SIMDIO and SMILE (sig. <0.001). The results of the study showed that 1. The human and organizational aspects did not show a significant contribution, 2. The technology aspect was the dominant factor influencing the benefits of the system.